After the Cold War : Amercian Foreign Policy, Europe and Asia - Cyr, Arthur I. (London Macmillian Press, 2000)
This work describes the changes in the international political arena after the Cold War and provides suggestions for policy analysis and definition in the future. There is extensive discussion of developments during the Reagan, Bush and Clinton administrations.
Include Notes, Bibliography and Index
Keywords: United States -- Asia -- Europe -- Diplomatic relations